Ants in Ecosystems and Agriculture: A Comprehensive Review - Soumik Dey Roy; Sourav Singh (International Journal of Insects, 2024)
Nearly 60% of the world’s habitats are underutilized. And current agricultural practices are blamed for contributing to soil carbon depletion and biodiversity loss. Climate change, habitat fragmentation, and other challenges hinder species development, leading to projected shifts in species distribution. This calls for alternative management strategies. The organizational structure of social insects, especially ants, offers a model for improved ants account for half of all insect biomass. It plays an important role in agricultural management superorganism. This article describes harvester ants and leafcutter ants, primarily the genus Lasius, and details their social structure. These ants collect plant sap with carbon-to-nitrogen (C/N) ratios of around 40 for their own sustenance and leaves with C/N ratios of 100 for fungus gardens and brood food. Their colony activities, such as burrowing, enhance soil aeration and drainage, while their fungus cultivation supports food preservation, disease control, and waste management. Ant colonies operate far from thermodynamic equilibrium, with physical, chemical, and biological gradients influencing nutrient cycling and biomass production. Leaf-cutter ants import 85–470 kg of plant material annually, primarily rich in carbon but low in nitrogen, facilitating nitrogen fixation and nitrate reduction. In nitrogen-deficient environments, ants rely on N2-fixing microorganisms to meet nitrogen demands. As a result, harvester, leaf cutter and honeysuckle ants are managed with low nitrogen ants present a sustainable agricultural approach, reducing soil carbon degradation and preventing increases in N2O emissions.
Keywords: Harvester Ants; Leaf-Cutter Ants; Social Insect Organization; Soil Carbon Management; Sustainable agriculture; nitrogen fixation